What's Stopping You? Being More Confident - Kelsey, Robert (Ascent Audio, 2020)
Confidence is not like an immunization jab. Its not something that can simply be injected into us through motivational exercises and positive thinking. Confidence comes almost exclusively from experience and self-knowledge. Millions of smart people are held back by a lack of this self-knowledge and unwittingly generate the kind of self-reinforcing behaviour that leads to low confidence. In the follow-up to the groundbreaking bestseller, Whats Stopping You?, with his very British approach to self-help, Robert Kelsey draws on extensive research and personal experience to provide a road map to help break down the barriers that make us shy away from achieving our true potential. Whats Stopping YouBeing More Confident? is aimed at helping to highlight the key reasons why you might be lacking confidence in the first place, what causes self-doubt or makes you feel less able than others. Then we are shown how to turn this around, by examining the traits that make someone confident, developing tactics for maintaining self-assurance and learning how to apply these in real-life practical situations. Confidence is about knowing what were good at, but also realizing what were not good at. Once we have come to understand and accept this, we can truly learn how to develop and sustain true confidence. Introduction Part One Explaining Poor Confidence 1 Scripts 2 Mindset 3 Reactions 4 The Journey Part Two The Alchemy of Confidence 5 Optimism and Resilience 6 Self-efficacy and Talent 7 Courage and Extraversion 8 Trust and Judgement Part Three Achievement 9 Identity 10 Goals 11 The Plan Part Four Situations 12 Shyness 13 Work One: Us 14 Work Two: Them 15 Dating Part Five Barriers 16 Prejudice 17 Procrastination 18 Depression 19 Stress and Anxiety 20 Hubris Additional Material: What the Psychologists Say.